2000
DOI: 10.1034/j.1399-3003.2000.16b15.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion capacity and haemodynamics in primary and chronic thromboembolic pulmonary hypertension

Abstract: The transfer factor of the lung for carbon monoxide (TL,CO) is decreased in patients with pulmonary hypertension. The pulmonary membrane diffusion capacity (Dm) and pulmonary capillary blood volume (Vc), were studied to establish: 1) the relative contribution of the components of the transfer factor to the decrease in TL,CO; 2) whether differences exist between primary pulmonary hypertension (PPH) and chronic thromboembolic pulmonary hypertension (CTEPH); and 3) the relationship between these parameters and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
60
7
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 22 publications
6
60
7
5
Order By: Relevance
“…Pulmonary vascular remodeling resulted in PASP, inducing changes to the right cardiac structure. Abbreviations as in Tables 1-3. causes poor alveolar perfusion [15,16]. Our findings were in agreement with Wang's study revealing that the miners with coal workers' pneumoconiosis had lower values of pulmonary function and higher prevalence of respiratory symptoms than did those without it, and a significant relationship was found between coal workers' pneumoconiosis and decrements in FVC and diffusing capacity.…”
Section: Discussionsupporting
confidence: 82%
“…Pulmonary vascular remodeling resulted in PASP, inducing changes to the right cardiac structure. Abbreviations as in Tables 1-3. causes poor alveolar perfusion [15,16]. Our findings were in agreement with Wang's study revealing that the miners with coal workers' pneumoconiosis had lower values of pulmonary function and higher prevalence of respiratory symptoms than did those without it, and a significant relationship was found between coal workers' pneumoconiosis and decrements in FVC and diffusing capacity.…”
Section: Discussionsupporting
confidence: 82%
“…It is therefore possible that the increased perioperative mortality observed by the present authors in patients with lower TL,CO was due to a higher degree of distal vasculopathy. STEENHUIS et al [15] were, however, unable to demonstrate a difference in DM or Vc in patients with idiopathic pulmonary arterial hypertension and CTEPH [15]. Furthermore, there was no significant difference in the TL,CO of patients in the present study with either operable or nonoperable disease (69.1 versus 68.4%; p50.72) [2].…”
Section: Discussioncontrasting
confidence: 41%
“…9,10,25 Because CTEPH is less associated with ventilation abnormalities, there should be no unventilated alveoli. 27 Indeed, in the present study, lung function tests and computed tomography of the lung showed no evidence of respiratory disease. Thus, intrapulmonary shunt, such as preexisting arterial-venous anastomoses and low ventilationperfusion units, is likely involved.…”
Section: Discussionmentioning
confidence: 83%